Psychometric properties of the TACT framework—Determining rigor in qualitative research - Daniel, Ben Kei; Asil, Mustafa; Carr, Sarah (Frontiers in Research Metrics and Analytics, 2024)
The credibility of qualitative research findings has been subject to ongoing criticism. Critics highlight the importance of maintaining rigour in qualitative research, emphasising explicit and detailed descriptions of the research process, including problem framing, study design, data collection, analysis, and reporting. Establishing universal guidelines for determining rigour in qualitative research remained a challenge as qualitative research often stems from diverse beliefs or paradigms, leading to various approaches to conducting such research. In addition, researchers' thought processes in qualitative research are often unrecorded, making it challenging to assess the quality of research outcomes. Furthermore, there is a lack of adequate pedagogical tools and analytical frameworks for postgraduate students, and those new to qualitative research can use them to assess the rigour of qualitative research processes and outcomes explicitly. To address this issue, this article draws from early work on the TACT framework developed to teach students the principles and indicators of rigour in qualitative research outcomes. TACT was specifically targeting postgraduate students and early career researchers. The present article reports on a scale designed to assess the TACT framework's psychometric properties, including its dimensions' stability and its implications as both a teaching and research tool.